Significance of sphingosine kinase 1 expression in feline mammary tumors - Chang, Yi-Chih; Chuang, Hsiao-Li; Yin, Ji-Hang; Liao, Jiunn-Wang; Chen, Ter-Hsin; Wang, Yu-Chih (BMC veterinary research, 2019)
Sphingosine kinase 1 (SPHK1) is an enzyme that converts pro-apoptotic ceramide and sphingosine into anti-apoptotic sphingosine-1-phosphate. There is growing evidence that SPHK1 activation promotes oncogenic transformation, tumor growth, chemotherapy resistance, and metastatic spread. High SPHK1 expression has been associated with a poor prognosis in several human cancers. In the present study, the expression level of SPHK1 was examined in feline mammary tumor (FMT) specimens, and the IHC expression level of SPHK1 was associated with the histological grade of FMTs. IHC analysis of 88 FMT cases revealed that the expression level of SPHK1 was upregulated in 53 tumor tissues (60.2%) compared to adjacent mammary tissues. SPHK1 expression in FMTs was significantly associated with histological grade, presence of lymphovascular invasion, and estrogen receptor negativity. Treatment of primary FMT cells with SPHK1 inhibitors reduced cell viability, indicating that SPHK1 acts to promote FMT cell survival. These results indicate that SPHK1 may play an important role in FMTs and may be a therapeutic target in cats with FMT. SPHK1 over-expression in breast cancer tissues is associated with a poor prognosis in humans. SPHK1 over-expression in more aggressive FMTs provides support for a potential role of SPHK1 inhibitors for the treatment of FMTs. Targeting SPHK1 has potent cytotoxic effects in primary FMT cells. These findings suggest that further examination of the role SPHK1 plays in FMTs will pave the way for the investigation of SPHK1 inhibitors in future clinical applications.